Prevalence of Pancreaticobiliary Maljunction (PBM) Among Sudanese Patients with Obstructive Jaundice in Ibnsina Specialized Hospital - Altayeb, Alaa Omer; Musaad, Abdulmagid Mohammed; Arabi, Nassir Alhaboob; Nagmeldin, Mohammed (مجلة الجزيرة للعلوم الصحية; مجلد 16 عدد 1 (2020), 2020)
Background: pancreaticobiliary maljunction is a congenital malformation in which the pancreatic and bile ducts join outside the duodenal wall. The common channel is long that leads to continuous reciprocal reflux between pancreatic juice and bile, resulting in various pathologic conditions in the biliary tract and pancreas. Methods and patients: This is a hospital based descriptive cross-sectional study, which was conducted in Ibn Sina Specialized Hospital over a period of one year (August 2018 – August 2019). The study included 62 patients. Data was collected using a constructed structure pretest questionnaire. Results: the mean age of the patients was 50.5, with male to female ratio 1:2.1. The majority of patients presented with the symptoms of bile obstruction .MRCP was done for all patients ; showed that CBD stones was the most common diagnosis in 82.3 %(n=51), followed by pancreatic carcinoma 6.5%(n=4). PBM found in 35.5 %( n= 22); the majority were type B 24.2% (n=15). In patients with CBD stones 82.3 %(n=51), PBM type B was the most common anomaly found 23.5% (n=12), the serum direct bilirubin was <5 mg/dl in 78%(n=40),and ALP more than 300 U/L in the majority of them. Conclusion : The prevalence of PBM is 35.5% , commonly found in female. The most common type of PBM is - type B, commonly found in patients with obstructive jaundice due to CBD stones.